Both‐Column Acetabular Fractures: Should Pelvic Ring Reduction or Acetabulum be Performed First?. Issue 11 (23rd September 2022) - Wan, Yizhou; Yu, Keda; Xu, Yi; Ma, Yan; Zeng, Lian; Zhang, Ziming; Yin, ZhenChun; Song, Qinghua; Chen, Kaifang; Guo, Xiaodong
Abstract: Objective: Both‐column acetabular fracture is a type that accumulates both the pelvis and acetabulum with complex fracture line alignment and has variant fracture fragments. The selection of different reduction landmarks and sequences produces different qualities of reduction. This study aims to compare the operation‐related items, quality of reduction, and hip functional outcome by using different reduction landmarks and sequences for management of both‐column acetabular fractures (BCAF). Methods: A consecutive cohort of 42 patients from January 2013 to January 2019 with BCAF were treated operatively with different reduction landmarks and sequences: pelvic ring fractures reduction first (PRFRF group) and acetabular fractures reduction first (AFRF group). Preoperative computer visual surgical procedures were applied. There were 22 patients in PRFRF group and 20 patients in AFRF group. The surgical details, complications, radiographic and clinical results were recorded. The quality of reduction was assessed by the Matta scoring system. The functional outcome was evaluated by the modified Merle d'Aubigné and Postel scoring system. The measurement data were analyzed using the t‐test of independent samples and rank‐sum test of ranked data. Results: The real reduction sequence in both groups was almost identical to the preoperative surgical procedures. The excellent/good quality of reduction in PRFRF group (21/22) was better than AFRF group (17/20). Operative time (152.3 ± 16.3 mins) and intra‐operative blood loss (639.5 ± 109.9ml) were significantly reduced in PRFRF group ( p  < 0.05). The incidence of deep vein thrombosis in PRFRF group (2/22) was less than AFRF group (4/20), but without statistical signification. Conclusion: Selection of an appropriate reduction landmark and sequence could result in better quality of reduction, operative time, and decreased blood loss during treatment of BCAF. Abstract : Selection of an appropriate reduction landmark and sequence could improve surgical efficiency.